The impact of flexibility and redundancy on improving supply chain resilience to disruptions - Kamalahmadi, Masoud; Shekarian, Mansoor; Mellat Parast, Mahour (International journal of production research, 2022)
This paper examines the relative impact on supply chain responsiveness of adding flexibility and redundancy. We seek to investigate the effectiveness of flexibility and redundancy in terms of minimising expected supply chain cost and maximizing expected service delivery when a supply chain is exposed to supplier and environmental disruptions. Compared to a supply chain that uses neither strategy and is exposed to supplier and environmental disruptions, both practices reduce expected lost sales, reduce expected total cost, and increase the expected service level. Our results show that the backup-suppliers practice is more effective than the flexible-suppliers practice, as measured by cost reduction and service-level improvement. In addition, we show that a hybrid practice created by adding some level of flexibility to a backup-suppliers practice is more desirable in terms of lowering pre-disruption investment, increasing the responsiveness of the supply chain, and lowering the expected total cost. Moreover, the result of the simulation shows that on average, the proposed stochastic model could decrease the company's total cost by 5.51%. It also shows that planning and investing in proactive demand management could decrease the company's total cost by 7.87%. Our findings provide insights into the contingencies that support implementation of each practice.